Research problems in prof. J. Matulionis competition of young mathematicians - Bronė Narkevičienė; Laima Papreckienė; Vilija Dabrišienė (Lietuvos Matematikos Rinkinys)
This article presents analysis results of research problems in prof. J. Matulionis competition of young mathematicians.